Aprils Mophie Model Improves Toothbrushing Skills Of Intellectual Disabilities Children: Is It Effective? - Nurhuda, Gusti Aprilisa; Sunarjo, Lanny; Fatmasari, Diyah; Sukini, Sukini; Ayun, Quroti (Jurusan Kesehatan Gigi, Poltekkes Kemenkes Semarang, 2024)
Children with intellectual disabilities are children with below average intelligence who experience a decline in intellectual function, difficulty communicating and adaptive behavior, arising before the age of 18 years. This child has not been able to brush his teeth properly, for that audio-visual media is used as a tool that can be seen and heard in his delivery, one of which is the development of April's Mophie model to improve the toothbrushing skills of children with moderate intellectual disabilities. Produce April's Mophie model as a learning medium to improve toothbrushing skills in children with moderate intellectual impairment. Research using Research and Development (R&D) method. Quasi-experimental research design (pre-post with control group design). Purposive sampling technique with 11 children of the intervention group and 11 children of the control group, with a duration of treatment given 21 days. Data were tested using Interclass Correlation Coefficient, Paired T-Test, Wilcoxon Test, and Mann-Withney. April's Mophie model showed a p-value of 0.000 which means that this model is feasible as an effort to improve toothbrushing skills in children with moderate intellectual impairment. The implementation of this model effectively increased the action of brushing children's teeth (p = 0.041), as well as a decrease in children's debris index (p = 0.037) compared to the control group. April's Mophie model effectively improves toothbrushing skills in moderately impaired children.